This preview has intentionally blurred sections. Sign up to view the full version.
View Full DocumentThis preview has intentionally blurred sections. Sign up to view the full version.
View Full DocumentThis preview has intentionally blurred sections. Sign up to view the full version.
View Full DocumentThis preview has intentionally blurred sections. Sign up to view the full version.
View Full Document
Unformatted text preview: Chapter 3. Vector Spaces Math1111 Linear Independence Proof of Thm 3.3.1 Proof of Theorem. Observe that c 1 x 1 + c 2 x 2 + ··· + c n x n = X c where c = ( c 1 c 2 ··· c n ) T . 1 ◦ (“if” part) Given X = ( x 1 x 2 ··· x n ) is nonsingular. Consider c 1 x 1 + c 2 x 2 + ··· + c n x n = ( * ) where c 1 , c 2 , ··· , c n are scalars. Chapter 3. Vector Spaces Math1111 Linear Independence Proof of Thm 3.3.1 Proof of Theorem. Observe that c 1 x 1 + c 2 x 2 + ··· + c n x n = X c where c = ( c 1 c 2 ··· c n ) T . 1 ◦ (“if” part) Given X = ( x 1 x 2 ··· x n ) is nonsingular. Consider c 1 x 1 + c 2 x 2 + ··· + c n x n = ( * ) where c 1 , c 2 , ··· , c n are scalars. Want to show c 1 = c 2 = ··· = c n = is the only choice for ( * ) to hold. . Chapter 3. Vector Spaces Math1111 Linear Independence Proof of Thm 3.3.1 Proof of Theorem. Observe that c 1 x 1 + c 2 x 2 + ··· + c n x n = X c where c = ( c 1 c 2 ··· c n ) T . 1 ◦ (“if” part) Given X = ( x 1 x 2 ··· x n ) is nonsingular. Consider c 1 x 1 + c 2 x 2 + ··· + c n x n = ( * ) where c 1 , c 2 , ··· , c n are scalars. ( * ) can be rewritten as X c = . Want to show c 1 = c 2 = ··· = c n = is the only choice for ( * ) to hold. i.e. c = . Chapter 3. Vector Spaces Math1111 Linear Independence Proof of Thm 3.3.1 Proof of Theorem. Observe that c 1 x 1 + c 2 x 2 + ··· + c n x n = X c where c = ( c 1 c 2 ··· c n ) T . 1 ◦ (“if” part) Given X = ( x 1 x 2 ··· x n ) is nonsingular. Consider c 1 x 1 + c 2 x 2 + ··· + c n x n = ( * ) where c 1 , c 2 , ··· , c n are scalars. ( * ) can be rewritten as X c = . Since X is nonsingular, i.e. X 1 exists, we have X 1 ( X c ) = X 1 c = . Chapter 3. Vector Spaces Math1111 Linear Independence Proof of Thm 3.3.1 Proof of Theorem. Observe that c 1 x 1 + c 2 x 2 + ··· + c n x n = X c where c = ( c 1 c 2 ··· c n ) T . 1 ◦ (“if” part) Given X = ( x 1 x 2 ··· x n ) is nonsingular. Consider c 1 x 1 + c 2 x 2 + ··· + c n x n = ( * ) where c 1 , c 2 , ··· , c n are scalars. ( * ) can be rewritten as X c = . Since X is nonsingular, i.e. X 1 exists, we have X 1 ( X c ) = X 1 c = . Hence ( * ) holds valid only for c 1 = c 2 = ··· = c n = . i.e. x 1 , ··· , x n are linearly independent. Chapter 3. Vector Spaces Math1111 Linear Independence Proof of Thm 3.3.1 Proof of Theorem. Observe that c 1 x 1 + c 2 x 2 + ··· + c n x n = X c where c = ( c 1 c 2 ··· c n ) T . 2 ◦ (“only if” part) Suppose x 1 , x 2 , ··· , x n is linear independent. Chapter 3. Vector Spaces Math1111 Linear Independence Proof of Thm 3.3.1 Proof of Theorem. Observe that c 1 x 1 + c 2 x 2 + ··· + c n x n = X c where c = ( c 1 c 2 ··· c n ) T ....
View
Full
Document
This note was uploaded on 04/30/2010 for the course MATH 1111 taught by Professor Dr,li during the Spring '10 term at HKU.
 Spring '10
 Dr,Li
 Math, Linear Independence, Vector Space

Click to edit the document details